Tatalaksana Komprehensif Gangguan Ginjal pada Pekerja Industri Gula - Badrul Munir; Meddy Setiawan; Febri Endra Budi Setyawan; Feny Tunjungsari (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2022)
Sugarcane workers have a higher risk of being exposed to pesticides where pesticides have high toxicity. One of the most common diseases is kidney disorders, including acute kidney injury and chronic kidney disease of unknown disease or known as mesoamerican nephropathy. This study is a literature review to determine the comprehensive management of kidney disorders in sugar industry workers. A comprehensive review was conducted by searching for national and international journals in the last 6 years which were identified according to the topic. Kidney disease in sugarcane workers can take the form of acute kidney injury in the acute phase and become chronic if the risk factors cannot be overcome. Risk factors for kidney disease in sugarcane workers are dehydration, pesticides, heat stress, strenuous physical activity, exposure to sugarcane burning smoke. Preventive steps that can be taken include providing good fluid intake, providing good rest areas, setting working hours, modifying special backpacks for water bottles, procuring appropriate personal protective equipment and using bagasse to reduce cadmium ions in pesticides. If kidney disease has occurred, monitoring and treatment is carried out according to the level of the disease so that it does not get worse. Sugar industry workers have various risks for the occurrence of kidney disease. Management that includes promotive, preventive, curative and rehabilitative can be done to provide comprehensive services for kidney disorders in sugarcane workers.